Notch effect to the fatigue life - Teh, Weng Khuin (2013)
This thesis is about the study on the notch effect to the fatigue life on the ASTM 1018 mild steel by using theoretical approach and experiment. The objective of this thesis is to study notch effect to the fatigue life. The thesis describes the stress concentration present on the notched specimen and its effect to the fatigue life on the specimen. The structural three-dimensional solid modeling of both smooth and notched specimen was developed by using the computer aided drawing software, SOLIDWORK 2012. The finite element analysis on the stress distribution was then performed by utilizing MSC NASTRAN. The maximum stress for specimens also was found by calculation using formula. The fatigue lives of both smooth and notched specimens were predicted by calculation using stress-life approach. Manson’s approach on notched specimen also used to predict the fatigue for notched specimens. The fabrication for both smooth and notched specimen is conducted by utilizing the computer numerical control lathe machine. Then, the fabricated specimens are tested in rotating bending fatigue by using fatigue test machine. The results were analysis by comparing to theoretical results and found that Manson’s approach is the more accurate way to predict the fatigue life for notched specimens. From the results, it found that the notched specimen will have a lot shorter fatigue life compared to the smooth specimen also the fatigue characteristic for both smooth and notch specimen is proven to be different from the observation of distinct fatigue behavior of them.